POSTGRADUATE COMMUNITY PSYCHIATRY TRAINING IN PAKISTAN - Rehman, Raza ur; Quraishy, Saadia; Siddiqi, Naim (Journal of Pakistan Psychiatric Society, 2022)
Closure of large psychiatric hospitals across UK, Europe and the United States has shifted the services for the care of psychiatric patients to general hospitals, community based public and private facilities and social sector organizations. Underpinning the process of deinstitutionalization and the development of community psychiatric services was the ethos of providing seamless, flexible services close to where people lived, led by their needs and with involvement of them and their care givers. In Pakistan, in-patient psychiatric facilities are scarce and community psychiatry is still in its initial stages of development so the burden of care is mostly beared by the families. There is a dearth of formalized training and skill set to work effectively in the community and this is reflected in the lack of exposure of our new generation of mental health professionals who are only trained in managing patients admitted in hospitals. In the light of recent guidelines and WHO recommendations it is imperative that community based psychiatric care be incorporated in the postgraduate psychiatry curriculum. This article describes the principles of training and syllabus.  However this can only possible by a proactive collaborative partnership between multiple public and private stake holders.